2001
DOI: 10.1590/s1020-49892001000900005
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic resistance mutations to antiretroviral drugs in HIV-1 B and non-B subtypes from Cuba

Abstract: Even though Cuba is generally considered an area where subtype B is dominant, we detected a high proportion of non-B subtype viruses. The low prevalence of resistance mutations to RTIs and PIs reflects the delay in introducing these drugs to Cuba. Multidrug resistance to RTIs was not found, so, as of now, the use of these drugs continues to be an option for Cuban patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In Cuba, moderate TDR prevalence to NRTIs (7.4%) was reported in a small survey performed in 1999 in 27 ARV-naïve subjects as part of a multi-country UNAIDS HIVDR study [ 24 ]. Nevertheless, a second survey performed in Havana in 2003 in 250 ARV naïve individuals showed low prevalence of NRTI TDR, and no evidence of TDR to NNRTIs and PIs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Cuba, moderate TDR prevalence to NRTIs (7.4%) was reported in a small survey performed in 1999 in 27 ARV-naïve subjects as part of a multi-country UNAIDS HIVDR study [ 24 ]. Nevertheless, a second survey performed in Havana in 2003 in 250 ARV naïve individuals showed low prevalence of NRTI TDR, and no evidence of TDR to NNRTIs and PIs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In one of the studies from Cuba 19 a prevalence of 5.3% of resistance-associated mutations to RTI was detected. In the other one, 13 including 103 HIV-1 samples obtained in 1999, the prevalence of resistance mutations was 27.6% to NRTI and 5.3% to NNRTI. These frequencies corresponded to a period in which antiretroviral treatment was not generalized in Cuba.…”
Section: Discussionmentioning
confidence: 98%
“…8,9 It has been recently reported that although subtype B continues to be predominant in this country, at least 10 genetic forms are circulating in Cuba, including subtypes A, C, F, G, and different RFs including CRF18_cpx (U pol ), CRF19_cpx (D pol ), BG (BG pol ), B/CRF19 (BD pol ), and B/CRF18 (BU pol ). [10][11][12] A previous study on plasma samples collected in 1999 in Cuba showed a low prevalence of resistance-associated mutations to reverse transcriptase and protease inhibitors (RTI and PRI) among B and non-B subtypes including 19 subtype A and 3 subtype C. 13 The introduction of highly active antiretroviral therapy (HAART) in 2001 was followed by a decrease in the AIDS mortality rate and in the incidence of opportunistic infections related to HIV/AIDS. At the end of 2003, a total of 1292 HIV-1 patients had received HAART, and consequently the emergence of HIV-1 drug resistance-associated mutations selected under treatment was probably occurring.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two Brazilian studies found NRTI resistance rates greater than 10%. 6,7 High baseline NRTI resistance rates have also been reported in Caribbean islands such as Martinique 20 and Cuba 21 where NRTI mutations were found in 24% and 7.4%, respectively. Equally high resistance rates have also been found in several drug-naive cohorts across the globe including the United States, [22][23][24][25] Switzerland, 26 Poland, 27 Germany, 28 Canada, 29 and Israel.…”
Section: Discussionmentioning
confidence: 99%